The mental health status among university students during open distance learning / Masshera Jamaludin ... [et al.] - Jamaludin, Masshera; Yusof, Syaidatul Afiqah; Kamaruddin, Harris Kamal; Ismail, Zulkifli; Abu Talip, Nur Khairunnisa (Universiti Teknologi MARA, Sabah, 2022)
Mental disorders are a significant contributor to the disease burden worldwide, and in Malaysia, it is the second-highest form of health problem. In response to COVID-19, the teaching delivery method has shifted from conventional to online learning (OL), resulting in a few challenges, especially among university students. This transition led to a problem associated with mental health conditions. Thus, this study aimed to identify the prevalence of mental health status between gender and faculty during online learning among the students of UiTM Perlis. A total of 362 male and female university students completed the electronic questionnaires, which include demographics and a 12-item General Health Questionnaire (GHQ-12), to assess students' general mental health status. The results showed that 71.3% of the students scored below four, which showed good mental health. However, 28.7% of students were categorized as having poor mental health. The findings have shown no significant difference (p<0.05) between university students' GHQ scores and gender. Other results revealed that the overall mean score of GHQ for all students was (2.40 ± 2.419), though there was no significant difference in the GHQ score among the six faculties of UiTM Perlis students. The findings have important implications.